Benefit of Negative Pressure Drain Within Surgical Wound After Cytoreductive Surgery for Ovarian Cancer. Issue 1 (January 2015) - Kim, Se Ik; Lim, Myong Cheol; Bae, Hyo Sook; Shin, Se Ra; Seo, Sang-Soo; Kang, Sokbom; Park, Sang-Yoon
<x xml:space="preserve">Abstract</x> Objective The objective of this study was to investigate the efficacy of subcutaneous negative-pressure wound drains on wound healing after cytoreductive surgery for ovarian cancer. Methods A retrospective study was performed on patients who underwent cytoreductive surgery for epithelial ovarian cancer, between 2012 and 2013. The patients were divided into 2 groups, according to using (n = 163) and not using (n = 37) of subcutaneous wound drains, and wound outcomes were analyzed. Results Patients' characteristics were not statistically different, except for the prolonged operative time in patients with wound drains (median, 395 vs 240 minutes; P = 0.001). A lower rate of wound infection (12.9% vs 27.0%; P = 0.032) was observed in the drain group. In the multivariate analysis, placement of subcutaneous wound drain was an independent prognostic factor for reducing wound complications: disruption (odds ratio [OR], 0.367; 95% confidence interval [CI], 0.145–0.929; P = 0.034) and wound infection (OR, 0.198; 95% CI, 0.068–0.582; P = 0.003). Bowel surgery at the time of cytoreductive surgery and prolonged operative time (≥360 minutes) were also associated with higher rates of disruption (OR, 2.845; 95% CI, 1.111–7.289; P = 0.029) and wound infection (OR, 4.212; 95% CI, 1.273–13.935; P = 0.019), respectively. Conclusions Installation of subcutaneous negative-pressure wound drain is an effective method to achieve clearer wound healing and less wound complications after cytoreductive surgery for ovarian cancer.